"Knife to Skin" Time Is a Poor Marker of Operating Room Utilization and Efficiency in Cardiac Surgery. Issue 6 (13th April 2015) - Luthra, Suvitesh; Ramady, Omar; Monge, Mary; Fitzsimons, Michael G.; Kaleta, Terry R.; Sundt, Thoralf M.
ABSTRACT Background Markers of operation room (OR) efficiency in cardiac surgery are focused on "knife to skin" and "start time tardiness." These do not evaluate the middle and later parts of the cardiac surgical pathway. The purpose of this analysis was to evaluate knife to skin time as an efficiency marker in cardiac surgery. Methods We looked at knife to skin time, procedure time, and transfer times in the cardiac operational pathway for their correlation with predefined indices of operational efficiency (Index of Operation Efficiency ‐ InOE, Surgical Index of Operational Efficiency ‐ sInOE). A regression analysis was performed to test the goodness of fit of the regression curves estimated for InOE relative to the times on the operational pathway. Results The mean knife to skin time was 90.6 ± 13 minutes (23% of total OR time). The mean procedure time was 282 ± 123 minutes (71% of total OR time). Utilization efficiencies were highest for aortic valve replacement and coronary artery bypass grafting and least for complex aortic procedures. There were no significant procedure‐specific or team‐specific differences for standard procedures. Procedure times correlated the strongest with InOE (r = −0.98, p < 0.01). Compared to procedure times, knife to skin is not as strong an indicator of efficiency. A statistically significant linear dependence on InOE was observed with "procedure times" only. Conclusions Procedure times are a better marker of OR efficiency than knife to skin in cardiac cases. Strategies to increase OR utilization and efficiency should address procedure times in addition to knife to skin times. doi: 10.1111/jocs.12528 (J Card Surg 2015;30:477–487)